2010
DOI: 10.1063/1.3336012
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical statistics and vortex structures in helical and nonhelical turbulences

Abstract: In this paper we conduct an analysis of the geometrical and vortical statistics in the small scales of helical and non-helical turbulence generated with direct numerical simulations. Using a filtering approach, the helicity flux from large scales to small scales is represented by the subgrid-scale (SGS) helicity dissipation. The SGS helicity dissipation is proportional to the product between the SGS stress tensor and the symmetric part of the filtered vorticity gradient, a tensor we refer to as the vorticity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…However, there are also experimental (Wallace et al 1992 on turbulent boundary layer, two-stream turbulent mixing layer, and turbulent grid flow) and numerical (Rogers and Moin 1987 on homogeneous turbulence and turbulent channel flow) studies that do not support this argument. Recently, Li (2010) used a filtering approach to study the helicity cascade and presented a geometrical analysis of both helical and nonhelical turbulences. Li (2010) identified some features which are unique in helical turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also experimental (Wallace et al 1992 on turbulent boundary layer, two-stream turbulent mixing layer, and turbulent grid flow) and numerical (Rogers and Moin 1987 on homogeneous turbulence and turbulent channel flow) studies that do not support this argument. Recently, Li (2010) used a filtering approach to study the helicity cascade and presented a geometrical analysis of both helical and nonhelical turbulences. Li (2010) identified some features which are unique in helical turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Other helical models have been devised recently [21][22][23][24]. For example, in [23], it is shown by assuming a Kolmogorov spectrum valid in the absence of rotation that the classical Smagorinsky model underestimates energy and helicity dissipation by 40 %, although numerically the effect seems smaller.…”
Section: Modeling Of Helical Flowsmentioning
confidence: 98%
“…Unsurprisingly, the helicity spectrum is much better described when using this helical subgrid scale model [22]; but one can remark that the growth rate of the total energy in the inverse cascade in rotating flows is also better estimated using this helical model. Finally, it has also been found that sub-grid helicity dissipation is responsible for observed asymmetries in the joint Probability Distribution Functions of the invariants of the vorticity gradient tensor, an asymmetry attributed to the geometry of twisted vortex tubes [24].…”
Section: Modeling Of Helical Flowsmentioning
confidence: 98%
“…While we provided significant evidence for the existence and importance of dynamic phase alignment, we stopped short of characterizing how it emerges from the nonlinear interactions. Dynamic phase alignment need not be regarded as necessarily alternative to other proposed paradigms for characterizing imbalanced turbulence [6,7,19,38,[46][47][48][49][50][51]. As an example, Ref.…”
mentioning
confidence: 99%